Daniel X. Watch the skies - Patterson, James, 1947-; Rust, Ned (Patterson, James, 1947- Daniel X novels, 2010)
A vengeful villain lives in the town of Holliswood and threatens to destroy it along with all of its citizens. Only Daniel X can deal with this made-for-TV tyrant who assembles an all-star team of his own, but even Daniel is not prepared for the enormity of this man's evil plan.